Discourse on Providing Fair Housing for The Middle Class: Housing Preferences of Young Lecturers in Peri-Urban Areas - Amelia Tri Widya; Stirena Rossy Tamariska; Antusias Nurzukhrufa; Yemima Sahmura Vividia (Jurnal Koridor, 2026)
Indonesia’s middle class, which comprises 66.35% of the total population and contributes 81.49% to national consumption, faces serious challenges in accessing decent housing in urban areas. Young middle-class individuals face housing unaffordability due to an 11.19% increase in housing prices over the past five years, while government housing policies still focus on Low-Income Communities, leaving the middle class as the "missing middle" without adequate assistance. This study aims to identify the housing preferences of young lecturers, who represent the urban middle class, analyze their adaptation strategies to address housing unaffordability, and uncover their implications for the discourse on housing equity. The study was conducted in the peri-urban area of ​​Bandar Lampung with 31 young lecturers from the Institut Teknologi Sumatera (ITERA) through in-depth interviews and the Analytical Hierarchy Process (AHP). The findings indicate that location is an absolute factor in the hierarchy of preferences, followed by price and security as fundamental needs. The majority of respondents still rent at up to 20 million rupiah per year, but aspire to housing in the 300-500 million rupiah range. This paradox of unaffordability forces respondents to adopt suboptimal strategies: renting while saving, building independently in remote locations with poor infrastructure, purchasing subsidized housing (downward adaptation), or living with their parents. This study confirms that housing affordability for the young middle class is a manifestation of imbalanced market failures and policies that ignore middle-class stratification.